REALIZAÇÃO DO EXAME PAPANICOLAU PELAS ACADÊMICAS DE ENFERMAGEM E MEDICINA DO CENTRO UNIVERSITÁRIO TOCANTINENSE PRESIDENTE ANTÔNIO CARLOS - Teodoro dos Santos Rodrigues, Heloise Mariane; Viana Araújo, Caio Roberto; Cerqueira de Oliveira, Evelling Lorena; Moreira Cunha, Luiza; Lucas Shangenis de Holanda Gama; Moreira Cunha, Nicole; Araújo de Melo Damasceno, Iangla (Brazilian Journal of Implantology and Health Sciences, 2024)
The preventive exam or Pap smear is a test carried out to detect the existence of any cellular changes in the cervix, which can be used to search not only for the existence of malignant or pre-malignant cellular changes, but also to search for the presence of the HPV virus. and several other gynecological infections. The present study is an exploratory, descriptive research of a cross-field nature, with a quantitative and qualitative approach. The objectives of the work were: to understand adherence to the Pap smear by nursing and medical students at UNITPAC - Araguaína, TO and to understand whether these students know about the importance and which pathologies are detected by the Pap smear. As a result we can more than half of nursing and medical students perform the exam routinely and in relation to knowledge about its importance as a diagnostic tool, it is concluded that the topic is known by students, however, it is still a subject that requires health education .